THE EFFECT OF COMPETENCE OF HUMAN RESOURCES, INFORMATION TECHNOLOGY AND ACCOUNTABILITY ON THE QUALITY OF REGIONAL FINANCIAL STATEMENTS WITH INTERNAL CONTROL SYSTEMS AS A MODERATION (STUDY IN DISTRICT OF GOWA) - Nurul Nadila Idward; Jamaluddin Majid; Mediyati Mediyati (Salewangang Institut Publishing, 2018)
This study aims to examine the influence of competence of human resources, utilization of information technology and accountability to the quality of local government financial statements. This research also aims to test the variable of internal control system of moderation of human resources competence relation, This study aims to examine the influence of competence of human resources, utilization of information technology and accountability to the quality of local government financial report. This research is a quantitative research with descriptive approach. The sampling technique used purposive sampling method. The sample in this research is employees of Regional Financial Management Agency (BPKD), while the number of questionnaires processed in this study as many as 34 pieces of questionnaires. The results showed that the competence of human resources, the utilization of information technology and accountability have a positive effect on the quality of local government financial statements. The internal control system is unable to moderate the competence variable of human resources and utilization of information technology to the quality of the regional financial report, but the internal control system is able to moderate the variable of accountability to the quality of local government financial report.